EU Bilateral Trade Agreements and Intellectual Property: For Better or Worse?
XIV, 303 p. 1 illus.
Keywords: This book focuses on a new generation of bilateral and regional agreements negotiated by the EU with developing countries and which include intellectual property (IP) provisions setting standards exceeding those of the TRIPS Agreement. The contributions critically analyse the IP standards found in these agreements; their potential for reforming the international IP system; the implications for the multilateral IP system and other areas of international law such as human rights; and the often neglected topic of implementing the IP obligations in these agreements.